(untitled) (MAUSAM, 1990)
During 11-13 March 1981 Telangana an Neighbourhood was affected by severe hailstorm caused extensive damage to life and property: In this paper an attempt has been made to bring out the synoptic situations. It. has been observed that the hailstorm was associated with marked upper air divergence, which was provided, by a jetstream, movement or a trough in the jet stream with axis located in the break of jet-core and strong Vertical wind shear. The low level convergence and interaction or airmasses or contrasting characteristics were provided by low level anticyclones over Bay or Bengal, Arabian Sea and surface low pressure area with north-south oriented trough and/or north-south low level upper air trough/wind discontinuity over the area.